The Effect of Communication Games and Self-Esteem towards Students’ Speaking Skill - Rifky Fakhrurrazy (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This research is an experimental research. This study aims to find out the effect of communication games as a teaching strategy and self-esteem toward students speaking skill at SMP Dr. Abd Ahmad PGAI Padang. The population of this research was students of grade VIII SMP Dr. Abd Ahmad PGAI Padang. The technique used is Cluster Random Sampling. The sample consists of students at VIII A as experimental class and VIII B as control class. In this research, the test is used to analize students’ speaking skill and questionnaire was used to collect self-esteem data. Data from the research were analyzed by using two-way t-test and ANOVA (ANOVA 2x2)4. The results of this research were (1) students taught with Communication Game have better speaking skills than students taught by conventional strategies, (2) the speaking skill of students with high self-esteem with Communication Game gives higher results than Conventional teaching strategies, (3) students 'speaking skills with low Self-Esteem with Communication Game gives higher results than conventional teaching strategies, and (4) there is no interaction between strategy and Self-Esteem in transactional text.